PENGARUH PENGGUNAAN MEDIA WAYANG GOLEK DAN MOTIVASI BELAJAR TERHADAP HASIL PAI MATERI SEJARAH KEBUDAYAAN ISLAM - Sohibul Bahri (QATHRUNÂ, 2019)
The main objectives in this study were to determine: (1) The effect of learning the use of wayang golek media on student learning outcomes in the SKI subject; (2) The effect of learning motivation on the results of PAI on the SKI material; (3) The influence of the interaction between the learning method using wayang golek media and learning motivation on the results of the Islamic Education Science material. The approach taken in this research is a quantitative approach. The method used is the Quasy Experiment method. The number of samples in this study is in accordance with the total population of 29 students at each school, so the research is called a population study. Data collection techniques were carried out through observation, questionnaires and tests. The data analysis technique used in this study was a two-way Vactorial analysis technique (ANAVA). The results and conclusion of this study indicate that the contribution of the learning effect of the wayang golek media usage model in influencing learning outcomes is 23,354. While the influence of learning motivation on learning outcomes is 10,779. The influence of the learning model using the wayang golek media and learning motivation together on learning outcomes is 5.203.